THE IMPACT OF TOURISM SECTOR ON REGIONAL INCOME INEQUALITY: EVIDENCE FROM CENTRAL JAVA INDONESIA - Santoso, Syalomo Ryan; Togarlaut, Lorentino (Universitas Tidar, 2025)
Income inequality is a more complex problem than poverty. The existence of income inequality will hamper the process of economic development and disrupt people's welfare. This study aims to determine the effect of the tourism sector on income inequality in the Regency / City of Central Java Province using the variables of the number of tourists, the number of tourism workers, economic growth, and Human Development Index (HD). This study uses Quantile Panel Regression using time series data 2015-2022 and cross-section data of 35 regencies/cities in Central Java Province. Based on the results of the research, it can be seen that the number of tourists has a positive and significant effect on middle income inequality, but has no effect on low and high income inequality, tourism labour has a negative and significant effect on low income inequality, but has no effect on middle and high income inequality, economic growth has a positive and significant effect on low income inequality, but has no effect on middle and high income inequality, HDI has a negative and significant effect on low income inequality and positive on high income inequality, but HDI has no effect on middle income inequality